Republic of Poland : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation for Poland highlights that with strong exports and robust consumption, its GDP growth picked up gradually, reaching 6.9 percent (year over year) in the first quarter of 2004. Nevertheless, investment growth remains moderate. Financial markets have been unsettled. Despite low inflation, long-term interest rates have risen since mid-2003, initially in response to the announcement of an expansionary 2004 budget and more recently to unsettled politics. The weak responses of investment and employment raise concern about fundamental impediments to the recovery.